Gagasan Intervensi Lanskap dalam Meningkatkan Resiliensi terhadap Banjir di Kawasan Cagar Budaya Asia-Afrika, Kota Bandung - Kusumah, Trinanda Sidik; Firmansyah; Gunaedi, Rhizky Annisa Ridyna (http://arl-faperta.ipb.ac.id/, 2025)
Asia-Afrika colonial heritage area is facing flood proneness that is influenced by Cikapundung River hydrological problem and increasing rainfall. The study aims to examine causal process of Asia-Afrika flood phenomenon, recommend possible implementation of landscape-based solution to mainly enhance local-scale fluvial and pluvial flood resilience, and predict possible impacts of those recommendations. Water resilience concept and historical review of cultural heritage is the basis of the study, while causal process is analyzed by Driver-Pressure-State-Impact-Response (DPSIR) method. DPSIR analysis identifies that impermeable land cover around Cikapundung upstream riverbanks, embankment failure debris, lack of water absorption function, and drainage system inadequacy for surface water runoff contributes as the cause of ankle-high flood in Asia-Afrika heritage area. Landscape-based recommendations for flood control are divided into planning and design scope, which are then focused on the implementation of stormwater street systems and riparian naturalization. Provided green areas can enhance physical and psychological quality. Green-blue infrastructure as flood-controlling element can reduce the cost allocation for post-disaster handling. Green space provision, riparian space allocation, and flood control elements can lead to some consequences, such as limited public space activities and relocation of affected inhabitants, indicating the complexity of social issues in the flood problem assessment.